Provider and user acceptability of intermittent screening and treatment for the control of malaria in pregnancy in Malawi. (December 2016) - Almond, Deborah; Madanitsa, Mwayi; Mwapasa, Victor; Kalilani-Phiri, Linda; Webster, Jayne; Kuile, Feiko; Paintain, Lucy
Abstract Background Malaria in pregnancy is a major cause of adverse maternal and fetal outcomes. Intermittent preventive treatment with sulfadoxine–pyrimethamine (IPTp-SP) is one of the control strategies promoted by WHO. In response to mounting resistance to SP, intermittent screening and treatment (ISTp) has been proposed as an alternative. The objective of this study was to explore the acceptability of ISTp for health workers and pregnant women. Methods Semi-structured interviews of ten health workers and five focus group discussions of 38 women enrolled in an ongoing trial comparing IPTp-SP and ISTp with dihydroartemisinin–piperaquine (DP) were conducted at two antenatal clinics in rural Malawi. All transcripts were coded and themes were identified using a content analysis approach. Results Amongst health workers, there were contrasting opinions on the preference of blood sampling methods, and the influence of method on reliability of diagnosis. The perceived greater effectiveness of DP compared to SP was appreciated, however concerns of user compliance with the full dose of DP in non-trial settings were raised. Despite the discomfort of repeated finger pricks, pregnant women were generally accepting of ISTp, particularly the chance for regular blood tests to check for infections and the perceived greater effectiveness with fewer side effects of DP compared to SP. Conclusion In the trial context, pregnant women tended to prefer ISTp-DP over IPTp-SP. Health workers were also accepting of ISTp-DP as an alternative to IPTp-SP in light of increasing SP resistance. However, reliability of stock, adherence to malaria test results and user adherence to the full course of DP may present barriers to successful routine implementation. Effective communication with health workers and between health workers, pregnant women and their communities will be essential for the acceptability of focused antenatal care, including the best malaria control measures available.